Intravenous dexamethasone fails to prolong psoas compartment block when assessed by objective pinprick sensory testing: a prospective, randomised, dose-dependent, placebo-controlled equivalency trial. (February 2018) - Turner, J.D.; Dobson, S.W.; Weller, R.S.; Russell, G.B.; Henshaw, D.S.
Abstract: Background: Recent studies have concluded that i.v. dexamethasone can prolong the duration of peripheral nerve blockade. We hypothesized that a 4 mg dose would equally prolong the duration of psoas compartment blocks (PCBs) when compared with 8 mg, and that both doses would prolong the duration when compared with placebo. Methods: This was a prospective, randomized, placebo-controlled, dose-dependent, equivalency trial with 115 patients undergoing total hip arthroplasty. The patients received a PCB. Subsequently, 15 patients received i.v. normal saline (placebo), 50 patients received i.v. dexamethasone 4 mg, and 50 patients received i.v. dexamethasone 8 mg. The primary outcome was the duration in hours of PCB, determined by serial pinprick assessments. Secondary outcomes included pain scores, time to first analgesic, and opioid consumption. An intention-to-treat-analysis (ITA) and per-protocol analysis (PPA) were performed. Results: The ITA showed that block duration in the 4 and 8 mg groups was equivalent [mean (standard deviation), 18.5 h (8.0) vs 18.1 h (7.1)]. However, neither group differed from placebo [19.6 h (6.7), (4 mg vs placebo), P =0.97; (8 mg vs placebo), P =0.77)]. Postoperative pain scores and opioid consumption were not different between groups. Time to first analgesic was not different between the 4 and 8 mg groups, or the 4 mg and placebo groups. The 8 mg group, however, had a longer time to first analgesic (median of 533 vs 432 min, P =0.047) when compared with placebo, although the significance was not observed in the PPA ( P =0.058). Conclusions: I.V. dexamethasone did not prolong PCB when duration was objectively assessed, or decrease total opioid consumption. However, dexamethasone 8 mg prolonged the time to first analgesic. Clinical trial registration: NCT 02464176.